การพัฒนาทักษะการอ่านออกเสียงคำในภาษาไทยของนักเรียนชั้นมัธยมศึกษาปีที่ 1 โรงเรียนศรีธรรมวิทยา ตำบลในเมือง อำเภอเมือง จังหวัดยโสธร - วงศ์น้ำคำ, กัณฐิกา; ดร., พระครูประสิทธิ์สีลคุณ; สองเมือง, ณัฏฐ์พิชญา; แสนสิ่ง, พีรพงษ์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 1 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 1 : มกราคม - เมษายน 2568, 2025)
This research aimed to study the level of word pronunciation in Thai and to compare the learning achievement in developing Thai word pronunciation skills among Mathayomsuksa 1 (Grade 7) students at Srithamwittaya School, Nai Mueang Subdistrict, Mueang District, Yasothon Province. The target group consisted of 50 Mathayomsuksa 1 students in the first semester of the 2024 academic year. This study employed a quasi-experimental research design. The results showed that the level of Thai word pronunciation and the learning achievement in developing word pronunciation skills among Mathayomsuksa 1 students in the first semester of the 2024 academic year at Srithamwittaya School were at a moderate level (m = 3.03, s = 0.79). Furthermore, the comparison of learning achievement in developing Thai word pronunciation skills revealed that students' ability to pronounce difficult words was also at a moderate level (m = 3.03, s = 0.79), which meets the 80/80 criterion.